2017
DOI: 10.1016/j.neubiorev.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent vulnerability to cardiovascular consequences of chronic emotional stress: Review and perspectives for future research

Abstract: Emotional stress has been recognized as a modifiable risk factor for cardiovascular diseases. Adolescence has been proposed as a developmental period of vulnerability to stress. This idea has been mainly supported by experimental research in animals demonstrating a higher impact of chronic emotional stress in adolescents compared with adults. Adolescent vulnerability is also based on evidence that stress during this developmental period affects development, so that enduring changes are found in adult animals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…Convergent clinical and preclinical studies have provided evidence that emotional stress is a modifiable risk factor for several cardiovascular dysfunctions (Sgoifo et al , ; Cohen et al , ; Crestani, ). Substances that modulate endocannabinoid neurotransmission have been indicated as a promising strategy for the treatment of cardiovascular dysfunctions (Carnevali et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Convergent clinical and preclinical studies have provided evidence that emotional stress is a modifiable risk factor for several cardiovascular dysfunctions (Sgoifo et al , ; Cohen et al , ; Crestani, ). Substances that modulate endocannabinoid neurotransmission have been indicated as a promising strategy for the treatment of cardiovascular dysfunctions (Carnevali et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Vicious Cycle of Stress, the right arc of the cycle represents the influence of stress on disease. Countless studies have experimentally demonstrated the negative impact stress has on disease progression, from cancer to cardiovascular disease, neurodegenerative disease and symptoms of aging (for review, see: Bjorntorp, 1997 ; Wahrborg, 1998 ; Girod and Brotman, 2004 ; Reiche et al, 2004 ; DiMicco et al, 2006 ; Pasquali et al, 2006 ; Goosens and Sapolsky, 2007 ; El Husseini and Laskowitz, 2014 ; Gupta and Morley, 2014 ; Prenderville et al, 2015 ; Herbert and Lucassen, 2016 ; Martocchia et al, 2016 ; Shin et al, 2016 ; Bortolato et al, 2017 ; Crestani, 2017 ). However, there are far fewer studies that address the left arc of the cycle.…”
Section: The Relationship Between Stress and Neurodegenerative Diseasmentioning
confidence: 99%
“…However, independently of the chronic stress paradigm, a similar small hypertensive effect (~10 mm Hg) was observed following long-term stress exposure in studies wherein baseline mean arterial pressure in control groups ranged from 95 to 120 mmHg (Grippo et al, 2008 ; Daubert et al, 2012 ; Duarte et al, 2015a ; Cruz et al, 2016 ) (Table 1 ). It has also been documented that cardiovascular dysfunctions induced by chronic stressors may be related to animals age (Crestani, 2016 ); hence, an influence of age (e.g., young vs. adult) was considered in this review (Table 1 ). However, the influence of age seems to be related to the type of chronic stressor.…”
Section: Cardiovascular Responses To Stress: Influence Of Chronicitymentioning
confidence: 99%